Barriers to the Implementation of "Newborn Individualized Developmental Care and Assessment Program" from the Perspectives of Nurses and Physicians - Nahid Foladi; Azam Shirinabadi Farahani; Manijeh Nourian; Elham Faghihzadeh; Leila Khanali Mojen; Sara Gholami; Fateme Goudarzi (Mashhad University of Medical Sciences, 2020)
Background: "Newborn Individualized Developmental Care and Assessment Program )NIDCAP(" is a caring approach based on individual neonatal behaviors that provides preventive measures for injuries caused by environmental stimuli. The present study aimed to investigate the barriers to the implementation of NIDCAP from the perspectives of nurses and physicians.Methods: This descriptive-comparative included 100 nurses and 21 physicians working in the Neonatal Intensive Care Unit (NICU). They were selected using a complete enumeration sampling method. Data were collected using a researcher-made questionnaire. The validity and reliability of the questionnaire were determined in this study. The data were analyzed in SPSS software (version 25) through descriptive and inferential statistics.Results: According to the nurses' perspective, the most imperative hurdles to the implementation of NIDCAP were environmental-structural, human resources, and communicational barriers. On the other hand, environmental-structural barriers obtained the highest score by the physicians and were placed in the first rank contrary to the management and human resources barriers that were placed in the second rank with equal scores. Furthermore, family-based care and communication were not considered obstacles to the implementation of the NIDCAP.Conclusion: According to the findings of this study, environmental-structural barriers were considered the main hurdles to the implementation of NIDCAP. Therefore, hospital administrators should make efforts to eradicate the existing barriers by making appropriate decisions in order to improve the quality of this method of care.